Azoic dye hosted in layered double hydroxide: physicochemical characterization of the intercalated materials - Mandal, Sujata; Tichit, Didier; Lerner, Dan A.; Marcotte, Nathalie (Langmuir, 2009)
Intercalation compounds were obtained by introduction of guest methyl orange (MO) into the interlayer space of host Mg/Al and Ni/Al layered double hydroxides (LDHs). Three synthesis methods of organic anion-LDH intercalation compounds, i.e., coprecipitation, reconstruction of the M(II)(Al)O mixed oxides, and anion exchange of LDH were compared. The former Method gives rise to a highly organized MO-intercalated Mg/Al LDH with an interlayer spacing of 2.43 rim and up to seven (001) reflection orders. Reconstruction or the mixed oxide by intercalation with MO in the restored LDH was only achieved with Mg(Al)O. In this case. a competitive adsorption of MO on the external Surface Of the crystals was also seen. On the other hand, intercalation compounds exhibiting interlayer spacing of 2.43 run were obtained with both Mg- and Ni-containing LDH using the anionic exchange method. The equilibrium and kinetic adsorption properties of the compounds were analyzed by UV-visible spectroscopy in anionic exchange experiments. According to the pseudo-second-order adsorption model, the amounts of adsorbed MO reach 3.82 and 2.83 mequiv/g for Mg- and Ni-containing LDHs, respectively, which are close to their respective anionic exchange capacity. The adsorption rates are on the same order of magnitude for the two LDHs (0.10-0.44 g mmol(-1) min(-1)), the equilibrium being reached in less than 60 min. The decomposition of MO by combustion of the organic moieties under an oxidizing atmosphere is delayed in Mg-containing MO-LDH hybrids when compared to the free MO molecule, showing that the thermal stability of MO species is enhanced after intercalation. In Ni-containing LDH, the main decomposition step of MO occurs 300 degrees C below that of Mg-containing LDH. This was rationalized in terms of a catalysis by the Ni-containing oxides formed during the thermal treatment. So these materials exhibit several advantage useful for the development of eco-friendly processes for the removal Of dyes from effluents of textile, plastic, and paper industries.